1978
DOI: 10.1093/jaoac/61.3.513
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Gas-Liquid Chromatographic Method for the Multidetermination of Antioxidants in Fats, Oils, and Dried Food Products

Abstract: A rapid quantitative method for determining 8 antioxidants in various food products is described. Two procedures are employed. The first involves the use of a glass wool precolumn to separate 3(2)-tert-butyl-4-hydroxyanisole, 3,5-di -tert - butyl - 4 - hydroxytoluene, 4 - hydroxymethyl- 2,6-di-tert-butylphenol, and mono-tertbutylhydroquinone (TBHQ) from nonvolatile residues resulting from direct injection of diluted sample or sample extracts into the gasliquid chromatographic (GLC) column. In the second proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The levels of antioxidants were determined for cornflake samples (Kline et al 1978). The results of this study established that BHT had been used in these samples.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The levels of antioxidants were determined for cornflake samples (Kline et al 1978). The results of this study established that BHT had been used in these samples.…”
Section: Resultsmentioning
confidence: 91%
“…Studies conducted in countries other than Turkey have given opposite results (Kline et al 1978;Page and Charbonneau 1989). In a study carried out in the USA, cheesy snack samples were evaluated for the presence of BHA and BHT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kline, et al (70) recently reported the silylation of TBHQ, TDPA, PG, THBP, and NDGA in a variety of food extracts, using a similar reagent to that of Sweeley, et al (64). The derivatives were quantitated on a 3% OV-225 column.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Although analytical methods including colorimetric (1)(2)(3), thin layer chromatography (TLC) (4,5), gas chromatography (GC) (6)(7)(8), and high pressure liquid chromatography (HPLC) (9)(10)(11)(12)(13) have been reported in the literature for the analysis of 2,6-di-tert-butyl-4-methylphenol (BHT) (and certain other antioxidants) in such substances as fats, oils, foodstuffs, packaging materials, etc., the recent publication of Sedea and Toninelli (14) was the only one found which dealt specifically with soap analysis. Their method was a standard addition, packed column GC procedure of the soap sample dissolved in methanol.…”
Section: Introductionmentioning
confidence: 99%